PENGARUH FAKTOR FINANSIAL TERHADAP PRESTASI KERJA PEGAWAI DI SEKRETARIAT DPRD KABUPATEN BONE BOLANGO - Bumulo, Frahmawati (Fakultas Ekonomi, UIN Maliki Malang, 2017)
Abstract: This study aims to know the influence of financial factors on employee performance at the sekretariatDPRD Kabupaten Bone Bolango. The methods used in this research is quantitative. The population of thisresearch is all employees of sekretariat DPRD Kabupaten Bone Bolango which need 25 sampling technique byusing simple random sampling. Data completion method used in this research is through questionnairedistribution to employees who become sample. The results of this study stated that the financial factorpositive and significant effect to employee performace at the sekretariat DPRD Kabupaten Bone Bolango.